EFFECT OF NITROSOGUANIDINE TREATMENT ON PATHOGENIC BEHAVIOUR OF XANTHOMONAS CAMPESTRlS PV. MALVACEARUM, INCITANT OF BACTERIAL BLIGHT OF COTTON - J. P. VERMA, S. K. DUTTAMAJUMDER* AND (Indian Phytopathology, 2002)
Effect of nitrosoguanidine (NG) mutagenesis on the pathogenicity of Xanthomonas campestris pv. maluacearum was studied. It indicated the possible involvent of chromosomal genes in the virulence determination. NG mutagenesis affected the virulence genes in both the direction, i.e., increase or decrease-in virulence and consequently changed the race number of isolate. Mutation rate of a marked locus str was increased from 2.28 X 10-9to 3.39 X 10-’ per cell per generation. Xcm was most vulnerable for a change against the host resistance gene B, and BNâ€¢ A yellow reaction (Y) in some cases replaced the hypersensitive reaction (HR), especially on the differential VII (101-102B). Probably, Y may be an intermediate reaction between SR and HR. Pigmentation of Xcm has no relation with its pathogenicity as mutants devoid of yellow pigment retained their pathogenicity.